171k views
5 votes
(12 4/9 + 1 2/9) + 3 5/9 =

2 Answers

5 votes
Ok so, first you want to add the fractions.
4/9 + 2/9= 6/9
Then, add the whole numbers.
12 + 1= 13
Put them together, and add that to 3 5/9
13 6/9 + 3 5/9
Again use the same method.
13 + 3= 16
6/9 + 5/9= 11/9
Put them together and get 16 11/9
Now, we need to change it out of a mixed number
11 รท 9= 1 with a remainder of 3
Add 1 to 16
And finally your answer 17 3/9

If you need to simplify it then it is 17 1/3
User Artory
by
5.6k points
3 votes
Remember PEMDAS, so evaluate the expression in the parenthesis first:

12 4/9 + 1 2/9= 13 6/9

Next, now that you're done with the parenthesis, evaluate 13 6/9 + 3 5/9:

13 6/9 + 3 5/9= 17 2/9
The answer to this equation is 17 2/9. hope this proves helpful :)


User Joelle
by
6.2k points